Comparison of m-Endo LES, MacConkey, and Teepol media for membrane filtration counting of total coliform bacteria in water. - Grabow, W O (1979)
Total coliform counts obtained by means of standard membrane filtration techniques, using MacConkey agar, m-Endo LES agar, Teepol agar, and pads saturated with Teepol broth as growth media, were compared. Various combinations of these media were used in tests on 490 samples of river water and city wastewater after different stages of conventional purification and reclamation processes including lime treatment, and filtration, active carbon treatment, ozonation, and chlorination. Endo agar yielded the highest average counts for all these samples. Teepol agar generally had higher counts then Teepol broth, whereas MacConkey agar had the lowest average counts. Identification of 871 positive isolates showed that Aeromonas hydrophila was the species most commonly detected. Species of Escherichia, Citrobacter, Klebsiella, and Enterobacter represented 55% of isolates which conformed to the definition of total coliforms on Endo agar, 54% on Teepol agar, and 45% on MacConkey agar. Selection for species on the media differed considerably. Evaluation of these data and literature on alternative tests, including most probable number methods, indicated that the technique of choice for routine analysis of total coliform bacteria in drinking water is membrane filtration using m-Endo LES agar as growth medium without enrichment procedures or a cytochrome oxidase restriction.